Brief Cognitive Screening Battery (BCSB) is a very useful tool for diagnosis of probable mild Alzheimer´s disease in a geriatric clinic - Fichman-Charchat, Helenice; Miranda, Cristina Vieira; Fernandes, Conceição Santos; Mograbi, Daniel; Oliveira, Rosinda Martins; Novaes, Regina; Aguiar, Daniele (Arquivos de Neuro-Psiquiatria, 2016)
The diagnosis of early signs of Alzheimer’s disease (AD) is a major challenge in a heterogeneous population.Objective To investigate the use of the Brief Cognitive Screening Battery (BCSB) for the diagnosis of mild AD in a geriatric outpatient unit of a public hospital in the city of Rio de Janeiro.Method BCSB was administered to 51 elderly adults with a clinical diagnosis of probable AD and 123 older adults without dementia (non-AD).Results AD patients performed worse than non-AD group in all BCSB tests, except Clock Drawing (p = 0.10). The ROC curves and Logistic Regression analysis indicated that delayed recall in the figure memory test was the best predictor, screening mild AD patients with sensibility and specificity superior to 80%.Conclusion The BCSB was accurate in identifying people with AD in a geriatric outpatient clinic at a public hospital, including elderly people with chronic diseases, physical frailty and cognitive impairment
Keywords: Alzheimer’s disease; aging; memory